Penegakan Hukum Pidana terhadap Tindak Pidana Penelantaran dalam Lingkup Keluarga dalam Perspektif Hukum Positif dan Nilai Sosial - Marzukri Hendrix; Isfandir Hutasoit; Edwar Kelvin (Dinasti Research, 2026)
This study aims to analyze criminal law enforcement regarding the crime of neglect within the family, viewed through the perspectives of positive law and social values. It employs a normative legal research method utilizing both statutory and conceptual approaches. Secondary data were analyzed qualitatively using a deductive reasoning approach. The findings indicate that legal provisions concerning family-based neglect are accommodated across various instruments, including the old and new Criminal Codes (KUHP), Law Number 35 of 2014 on Child Protection, and Law Number 23 of 2004 on the Elimination of Domestic Violence. However, the Child Protection Law serves as the most appropriate lex specialis for addressing child neglect, as it specifically regulates the subjects involved, the nature of the acts, and the applicable criminal sanctions. Conversely, law enforcement practice faces obstacles, such as a tendency to resolve cases through mediation and the perception of neglect as a private family matter, which often prevents criminal prosecution. From the perspective of social values, cultural norms regarding family dynamics influence law enforcement, creating a gap between legal norms and their actual implementation. In conclusion, consistent application of legal principles and the strengthening of the role of law enforcement officials are essential to ensure optimal and equitable protection for children who are victims of neglect. The study implies a need to harmonize criminal law policies and strengthen child protection mechanisms based on a restorative approach, while prioritizing the principle of the best interests of the child. Furthermore, enhanced coordination and synergy among law enforcement agencies, child protection institutions, and the community are required to ensure the sustained effectiveness of law enforcement against the crime of child neglect.